VERIFICAÇÃO AUTOMATIZADA DE REQUISITOS REGULAMENTARES EM PROJETOS HOSPITALARES COM O USO DE BIM - Soliman Junior, João; Fonseca, Vitor; Formoso, Carlos; Tzortzopoulos, Patricia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The impact of the design and the built environment on health outcomes has been widely discussed in the literature. The design phase for healthcare buildings is essential as it can contribute positively to the health and well-being of its users. However, healthcare projects are mostly undertaken based on manual methods, which are not capable of dealing with its complexity. Design reviews are a fundamental part of healthcare projects assessment. When these are developed manually they tend to be inconsistent, take a long time and are prone to errors. The aim of this paper is to explore the role of BIM-based automated rule checking in a hospital design. The main contribution is related to identifying the potential and limitations of using current software to perform automated tasks on healthcare design review. Additionally, it was possible to understand how other related BIM-based activities could support the development of better designs, by using geometry-based visualization, as well as semantic-rich information repositories.